SPIRITUAL AND CULTURAL APPROACH TO PREVENT BULLYING IN ELEMENTARY SCHOOL - Arrosih; Muhamad Ahyar Rasidi; Rizal M. Suhardi (Universitas Islam Negeri Mataram, 2023)
Bullying is widespread in various walks of life, disturbing, and can potentially interfere with achieving educational goals in elementary schools, depending on the form and impact. This study aims to explore types of bullying and spiritual and cultural approaches to prevent it in elementary schools with a case study approach. Data collection techniques using observation, interviews, and documentation are processed through data reduction, presentation, and conclusion. The study results illustrate that the types of bullying include verbal, social, and physical, with a percentage that has no significant impact and is controlled. In terms of gender, 75% of bullying is done by men. To prevent it from remaining under control, schools familiarise themselves with various religious programs through the Imtaq program and integrate spiritual messages into the learning process. Likewise, a cultural approach can foster love and wisdom through local values, including cultural attractions